Enzymatic biodegradation of used engine oil using a novel lipase derived from renewable feedstocks - Tracy, Preetanshika; Dasgupta, Diptarka; Ashok, Patel Pratima; More, Snehal; Sarkar, Bipul; Porwal, Jyoti; Tripathi, Deependra (World Journal of Microbiology & Biotechnology, 2025)
This study introduces an eco-friendly enzymatic approach for biodegrading used engine oil, utilizing a novel lipase from the mesophilic yeast strain Pichia Caribbica. The yeast was cultured in detoxified corncob hydrolysate with used cooking oil as an inducer. OVAT study confirmed that the optimal pH and temperature for lipase production by the strain was 7.0 and 25 degrees Celsius, respectively, with lipase activity of 70 IU/mL. The enzyme effectively degraded similar to 46% of used engine oil over a period of 15 days. Gas Chromatography-Mass Spectrometry (GC-MS) and FT-IR analysis confirmed a significant reduction in hydrocarbon concentrations and the emergence of new functional groups, confirming the enzyme's ability to degrade complex hydrocarbons into less toxic derivatives. These findings highlight the lipase's potential as an effective biocatalyst for eco-friendly bioremediation of oil-contaminated environments, such as soils and aquatic systems, while also emphasizing its role in environmental management through the reuse of waste by-products in enzyme production, thus reducing the environmental impact of improper waste disposal.
Keywords: Biodegradation; Lipase; PC5703; Used cooking oil; Used engine oil